Assessment of risk of depression and diabetes among overweight and obese subjects with unsuccessful efforts to reduce body weight: Observation from clinical trial participants of weight loss intervention - Ranakishor Pelluri&&, Kongara Srikanth, Jithendra Chimakurthy, Vanitharani Nagasubramanian (Journal of Applied Pharmaceutical Science, 2021)
Paucity of data in context to depression and diabetes among obesity (OB) or overweight (OW) subjects with unsuccessful efforts to reduce body weight is unclear. Considering this, we evaluated the relationship between depression and diabetes risk among those populations. The vital and biochemical parameters, including lipid profile, homeostatic model assessment, were measured for eligible screened subjects who participated in the trial of weight loss intervention at first visit. Risk associated with depression and type-2 diabetes was assessed by self-reported Patient Health Questionnaire scale and American Diabetes Association diabetic risk score respectively. In our study, out of 165 individuals, 59 (35.75%) were OW and 106 (64.25%) were OB, as per the World Health Organization criteria. The OW and obesity males have greater risk of pre-diabetes or diabetes (odds ratio: 4.55% and 3.15%, 95% confidence intervals: 1.45–14.21 and 1.33–7.52) (p = 0.009 and 0.008). The body mass index (BMI) is strongly associated with depression and diabetes (p = 0.0001*). Insignificant association was observed between insulin resistance/diabetic among the depressive obese subjects (p > 0.05). Obesity or OW were found to link with risk of depression and the abnormal BMI was substantially amplifying the risk of diabetes.
Keywords: Depression, diabetic risk, overweight, obesity